2021
DOI: 10.1101/2021.12.05.471275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prdm16 amplifies Notch signaling and suppresses venous lineage specification to prevent arteriovenous malformations during vascular development

Abstract: Rationale: Proper functionality of the circulatory system requires correct arteriovenous (AV) endothelial cell (EC) differentiation. While Notch signaling and its downstream effector Hes-Related Family bHLH Transcription Factor with YRPW Motif (Hey)2 favor arterial specification, transcription factor (TF) chicken ovalbumin upstream transcription factor 2 (Coup-TFII) inhibits canonical Notch activity to induce venous identity. However, transcriptional programs that compete with Coup-TFII to orchestrate arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…Previous studies found an interplay between Prdm16 and Notch signaling in different systems. Prdm16 modulates Notch signaling during arterial specification 49,50 . Loss of the Notch target genes, Hes1, 3 & 5 cause downregulation of Prdm16 expression in the ventricular zone of the developing telencephalon 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found an interplay between Prdm16 and Notch signaling in different systems. Prdm16 modulates Notch signaling during arterial specification 49,50 . Loss of the Notch target genes, Hes1, 3 & 5 cause downregulation of Prdm16 expression in the ventricular zone of the developing telencephalon 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Prdm16 modulates Notch signaling during arterial specification. 49 , 50 Loss of the Notch target genes, Hes1, 3 & 5 cause downregulation of Prdm16 expression in the ventricular zone of the developing telencephalon. 51 Prdm16 has also been demonstrated to be a key regulator in the cell fate choice between skeletal muscle and brown adipose in common progenitors during embryogenesis and also influences beige adipose function and its metabolic function postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…29 In fact, the combined genetic effect of these 2 variants was a 5 mm Hg reduction in mean arterial pressure, and as a result a reduced risk of CAD, peripheral arterial disease, and stroke. In addition to the regulation of vascular tone, functional studies in cultured ECs have also implicated EC angiogenesis ( PRDM16 , 30 FLT1 loci), EC barrier function ( JCAD , 31 ARHGEF26 32 ), and leukocyte adhesion ( PLPP3 33 ) in atherosclerosis.…”
Section: Slow Functional Characterization Of Individual Ec-relevant C...mentioning
confidence: 99%